Balance of Thread on the Surface of Fabric - Sanovar, Khamraeva; Kodir, Muminov; Raximaxon, Хаytmetova; Mushtaribonu, Shaxobiddinova (International Journal on Orange Technologies, 2023)
In the article, on the basis of the formula of resistance of materials and mechanics of continuous media, assessments are given for the strength of the fabric and their optimal parameters are determined, which are substantiated theoretically. The static equilibrium of tissues at different internal pressure values is considered and the main theoretical formulas that allow evaluating tissues are indicated. Here we offer to find the optimal structure of the fabric, calculation of selection of geodesic lines. Now we’ll determine exertion of threads at inner pressure. For this the main laws of mechanics of deformed hard body and equations of mathematic physics are used.